Study of Commercially Available Lobelia chinensis Products Using Bar-HRM Technology - Sun, Wei; Yan, Song; Li, Jingjian; Xiong, Chao; Shi, Yuhua; Wu, Lan; Xiang, Li; Deng, Bo; Ma, Wei; Chen, Shilin (Frontiers in Plant Science, 2017)
There is an unmet need for herbal medicine identification using a fast, sensitive, and easy-to-use method that does not require complex infrastructure and well-trained technicians. For instance, the detection of adulterants in Lobelia chinensis herbal product has been challenging, since current detection technologies are not effective due to their own limits. High Resolution Melting (HRM) has emerged as a powerful new technology for clinical diagnosis, research in the food industry and in plant molecular biology, and this method has already highlighted the complexity of species identification. In this study, we developed a method of species specific detection of L. chinensis using HRM analysis combined with internal transcribed spacer 2 (ITS2). We then applied this method to commercial products purporting to contain L. chinensis. Our results demonstrated that HRM can differentiate L. chinensis from six common adulterants. HRM was proven to be a fast and accurate technique for testing the authenticity of L. chinensis in herbal products. Based on these results, a HRM approach for herbal authentication is provided.